2021
DOI: 10.1111/ijfs.15186
|View full text |Cite
|
Sign up to set email alerts
|

Role of pulses to modulate the nutritive, bioactive and technological functionality of cereal‐based extruded snacks: a review

Abstract: Summary Pulses hold excellent nutritive potential owing to high‐quality protein content, dietary fibre, minerals, vitamins, oligosaccharides, polyphenols, tannins, phytosterols and several other bioactive constituents. These bio‐functional compounds impart significant health benefits by reducing the risk of several chronic complications such as hypertension, cancers, cardiovascular diseases and neurological concerns mainly through anti‐oxidative and radical scavenging mechanisms. These high protein ingredients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Comparatively, higher GCV weasobtained for weeds (447 Kcal/100 g) than those from cereals, pulses and beans (379 to 397 Kcal/ 100 g). Similar energy content was reported in the literature (Tacer-Caba et al, 2015;Venkidasamy et al, 2019;Sharma et al, 2021).…”
Section: Energy Contentsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparatively, higher GCV weasobtained for weeds (447 Kcal/100 g) than those from cereals, pulses and beans (379 to 397 Kcal/ 100 g). Similar energy content was reported in the literature (Tacer-Caba et al, 2015;Venkidasamy et al, 2019;Sharma et al, 2021).…”
Section: Energy Contentsupporting
confidence: 89%
“…Specifically, Venkidasamy et al (2019) found that pulses are rich in potassium, calcium, magnesium, phosphorous and iron. This kind of seeds also contains bioactive compounds such as phenolic compounds (Sharma et al, 2021). Ram ırez-Ojeda et al (2018) reported that according to the contributions to Dietary Reference Intakes, legumes were proper sources of iron, calcium, manganese and zinc.…”
Section: Introductionmentioning
confidence: 99%
“…Other beneficial physiological effects. The bioactive peptides, amino acids and phenolic compounds contained in legumes make it anti-inflammatory and the presence of bioactive peptides, phenols and SCFAs also makes it pro-apoptotic (Sharma et al, 2022). At the same time, the presence of phenolic acids, flavonoids and other phytochemicals in legumes gives it antioxidant properties (Sharma et al, 2022;Atudorei & Codin a, 2020).…”
Section: Physiological Functions Of Legumes Flourmentioning
confidence: 99%
“…Cowpea seeds are a good source of health‐promoting bioactive compounds, mainly phenolic acids derivatives (148–1176 μg g −1 ), flavonol glycosides (27–1060 μg g −1 ), and peptides. These polyphenols and peptides have a significant anti‐inflammatory effect, and benefits against cancer, diabetes, and cardiovascular disease (Awika & Duodu, 2017; Sharma et al ., 2021). Apart from the macronutrients, cowpea provides micronutrients, including vitamins (Vitamin B complex, C, carotenoids, E) and minerals (potassium, phosphorus, calcium, sulphur, magnesium, iron, zinc, manganese, and copper) (Gonçalves et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%